THE IMPORTANCE OF FISH OIL IN THE HUMAN BODY AND METHODS FOR DETERMINING THE QUALITY OF FATS (Innovative Technologica: Methodical Research Journal, 2021)
In this study, we examined the importance of fish oil and fish products in the human body. Fish products are excellent food in terms of protein, vitamin D and micronutrients (even in small amounts, which are very important for the human body). It contains minerals such as phosphorus, sulfur and vanadium that support human growth and tissue development.